“Welcome to Our Home!”: Staging Practices at Louisa May Alcott’s Orchard House - Klara Stephanie Szlezák (Current Objectives of Postgraduate American Studies)
Louisa May Alcott’s Orchard House, today a major site of literary tourism in New England, reaches out to and draws in visitors who wish to experience first-hand the premises where the Alcotts lived and where Little Women“, one of America’s favorite novels, was written. The essay investigates to what extent, however, this and other house museums rely on staging and argues that a close reading of the material culture reveals the limitations of a claim for ‘authenticity.’